Community seed banks: sharing experiences from North and South. - Andersen, R.; Shrestha, P.; Otieno, G.; Nishikawa, Y.; Kasasa, P.; Mushita, A. (DIVERSIFOOD, 2018)
Note full title of report is: Community Seed banks: Sharing experiences from North and South. Report from a side event held 1 November 2017 during the Seventh Session of the Governing Body of the International Treaty on Plant Genetic Resources for Food and Agriculture in Kigali, Rwanda. Paris: DIVERSIFOOD.